Bacteriological Quality Assessment of Kilishi Produced in Kunchi Local Government Area, Kano State, Nigeria - Dahiru A. T.,; Maigari A. K. (UMYU Journal of Microbiology Research)
Dried roasted sliced meat (Kilishi) is a popular meat product in Northern Nigeria that is relished locally and internationally. However, the abundance of a number of nutrients that favour the establishment, growth and proliferations of microorganisms, makes it a vehicle for transmitting food borne illness. This study was aimed at determining the microbiological quality of Kilishi in Kunchi Local Government Area, being one of the well-known Kilishi production town in Kano State. The experimental lay-out for the study was a completely randomised design in which a total of 15 freshly prepared Kilishi samples (100g each) were collected from three well known retail locations, identified as A (Malikawa Garu), B (Shuwaki) and C (Kunchi town), respectively. The samples were assessed for their microbiological quality according to standard procedures. Results for total aerobic mesophilic bacterial count (APC) cfu/g show Location A had 3.92×105cfu/g, Location B had 4.83×105cfu/g, Location C 5.43×105cfu/g. The results for the total coliform counts(TCCs) revealed30 MPN/g for Location A, 37 MPN/g for Location B and 50 MPN/g for Location C. Biochemical analysis confirmed the presence of Escherichia coli, Klebsiella specie, and Staphylococcus specie in all the three locations, while Enterobacter was detected in Location C. Our finding indicates serious contamination of kilishi products at retail outlets which could be of public health concern. Therefore, good production practices, packaging and storage were recommended.